Knowledge development in early childhood : sources of learning and classroom implications - Pinkham, Ashley M.; Kaefer, Tanya; Neuman, Susan B. (New York : The Guilford Press, 2012)
"Synthesizing cutting-edge research from multiple disciplines, this book explores how young children acquire knowledge in the "real world" and describes practical applications for early childhood classrooms. The breadth and depth of a child's knowledge base are important predictors of later literacy development and academic achievement. Leading scholars describe the processes by which preschoolers and primary-grade students acquire knowledge through firsthand experiences, play, interactions with parents and teachers, storybooks, and a range of media. Chapters on exemplary instructional strategies vividly show what teachers can do to build children's content knowledge while also promoting core literacy skills"--
"Subject Areas/Keywords: classrooms, content areas, curriculum, developmental psychology, early childhood education, early intervention, early literacy, educational psychology, families, family, instructional methods, knowledge acquisition, parents, pedagogy, play, preschool, teaching, texts, vocabulary, young children DESCRIPTION Synthesizing cutting-edge research from multiple disciplines, this book explores how young children acquire knowledge in the "real world" and describes practical applications for early childhood classrooms. The breadth and depth of a child's knowledge base are important predictors of later literacy development and academic achievement. Leading scholars describe the processes by which preschoolers and primary-grade students acquire knowledge through firsthand experiences, play, interactions with parents and teachers, storybooks, and a range of media. Chapters on exemplary instructional strategies vividly show what teachers can do to build children's content knowledge while also promoting core literacy skills"--
Part I. Sources of Children's Knowledge: 1. What you see is what you get: learning from the ambient environment / Tanya Kaefer; 2. Learning through play: procedural versus declarative knowledge / Jennifer Van Reet; 3. How children understand and use other people as sources of knowledge: children's selective use of testimony / Sherryse L. Corrow, Jason Cowell, Sabine Doebel, and Melissa A. Koenig; 4. Beyond pedagogy: how children's knowledge develops in the context of everyday parent-child conversations / Maureen Callanan, Jennifer Rigney, Charlotte Nolan-Reyes, and Graciela Solis; 5. Drawing on the arts: less-traveled paths toward a science of learning? / Jessa Reed, Kathy Hirsh-Pasek, and Roberta Michnick Golinkoff; 6. Learning by the book: the importance of picture books for young children's knowledge acquisition / Ashley M. Pinkham; 7. Television and children's knowledge / Heather J. Lavigne and Daniel R. Anderson -- Part II. Promoting Knowledge Development in the Classroom: 8. Four play pedagogies and a promise for children's learning / Kathleen Roskos and James Christie; 9. The research-reality divide in early vocabulary instruction / Tanya S. Wright; 10. The contributions of curriculum to shifting teachers' practices / David K. Dickinson, Erica M. Barnes, and Jin-Sil Mock; 11. Scaffolding preschoolers' vocabulary development through purposeful conversations: unpacking the ExCELL model of language and literacy professional development / Barbara A. Wasik and Annemarie H. Hindman; 12. Building knowledge through informational text / Nell K. Duke, Anne-Lise Halvorsen, and Jennifer A. Knight; 13. Knowledge acquisition in the classroom: literacy and content-area knowledge / Carol McDonald Connor and Frederick J. Morrison; 14. Building literacy skills through multimedia / Rebecca Silverman and Sara Hines.
Includes bibliographical references and index.
Keywords: Early childhood education; Experiential learning; EDUCATION / Preschool & Kindergarten; PSYCHOLOGY / Developmental / Child; LANGUAGE ARTS & DISCIPLINES / Literacy; EDUCATION / Educational Psychology